Development of design solution for mine workings support repair and recovery in case of local massif deformations - Tsibaev Sergey (EDP Sciences, 2021)
The article describes the causes of occurrence and forms of geomechanical processes manifestation in surrounding coal-rock massif of mine workings supported by anchor support. Based on long-term field observations, six forms of typical deformations of the surrounding massif have been established. Design solutions to strengthen the anchor support or complete reinforcement of damaged sections of mine workings during geomechanical processes of local felling have been developed. They include: installation scheme, substantiation of parameters and list of used reinforcement elements; technology of work, a list of equipment used.